Preparation and application of composite ion conduction membrane

By adding catalyst and aromatic amines to the preparation process of the ion conductive film, and using binary aromatic carboxylic acids to form a micro-phase separation structure, the problems of insufficient ion selectivity and high cost in existing films in liquid flow batteries are solved. It achieves efficient and stable improvement in flow battery performance and mechanical performance.

CN119192639AActive Publication Date: 2024-12-27ANHUI CONCH CLEAN ENERGY TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411297679.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing ion conductive films have problems such as insufficient ion selectivity and high cost in flow batteries, and it is difficult to have high conductivity and excellent vanadium ion barrier properties, which limits the efficient and stable operation of flow batteries and industrial applications.

Method used

The catalyst and quaternary aromatic amine are mixed and heated and stirred under an inert atmosphere. The compound ion conductive film is prepared by casting method. Add additives to the film to form a micro phase. Separate structures and optimize pore distribution and proton conductivity.

Benefits of technology

The prepared composite ion conductive film exhibits high conductivity, excellent vanadium ion conductivity and excellent mechanical properties. The Coulomb efficiency, voltage efficiency and energy efficiency are significantly improved, and the tensile strength and elongation at break are also greatly improved, surpassing the current situation. Membrane properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192639A_ABST
    Figure CN119192639A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of a composite ion conduction membrane. Comprising the following steps: mixing a catalyst and quaternary aromatic amine in an inert atmosphere, and heating and stirring for reaction to obtain a homogeneous system; adding binary aromatic carboxylic acid or a derivative thereof into the homogeneous system, heating, stirring and reacting, and washing to obtain base membrane resin; and dissolving the base membrane resin by adopting an organic solvent, adding an additive, performing ultrasonic treatment, and performing tape casting to obtain the target ion conduction membrane. The prepared ion conduction membrane has good electrical properties and mechanical strength, the coulombic efficiency can reach 95.6%, the voltage efficiency can reach 93.2%, the energy efficiency can reach 87.9%, the tensile strength exceeds 110 MPa, the elongation at break reaches up to 2877%, and all the properties are remarkably higher than those of an existing ion conduction membrane. The method can be applied to preparation of various flow batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an ion conducting membrane, and in particular to a method for preparing a composite ion conducting membrane for a liquid flow battery. Background Art

[0002] In the core structure of flow batteries, ion conduction membrane plays a vital role. It is not only a barrier for the mutual penetration of vanadium ions in the positive and negative electrolytes, but also a channel for hydrogen ions to flow and form a closed loop of the battery. Its performance is directly related to the overall efficiency of the entire battery system. An ideal ion conduction membrane should combine high ion selectivity, excellent ion conduction efficiency, excellent chemical stability and economical cost. Existing commercial membrane materials, such as the perfluorosulfonic acid ion conduction membrane (Nafion) produced by DuPont in the United States, have stable performance, but the insufficient ion selectivity and high cost have become bottlenecks restricting their widespread industrial application. Non-fluorine ion conduction membranes have the characteristics of low cost, high thermal stability and mechanical strength, and good ion selectivity. This type of membrane material achieves precise separation of conductive ions and protons through fine pore size screening mechanism and charge repulsion effect. However, its relatively low conductivity is still a key factor restricting its further commercial application. Therefore, the current research focus is on developing an ion-conducting membrane that has both high conductivity and excellent vanadium ion barrier properties, in order to further reduce the overall cost while ensuring the efficient and stable operation of the flow battery, and promote the industrial application of all-vanadium liquid flow battery energy storage technology. Summary of the invention

[0003] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a composite ion conductive membrane, so as to solve the problem of how to prepare a composite ion conductive membrane. Another purpose of the present invention is to propose an application of a composite ion conductive membrane in a liquid flow battery, so as to solve the problem of how to improve the performance of the liquid flow battery.

[0004] Technical solution: A method for preparing a composite ion conducting membrane according to the present invention comprises the following steps:

[0005] (1) Under an inert atmosphere, a catalyst and a quaternary aromatic amine are mixed, and heated and stirred to react to obtain a homogeneous system;

[0006] (2) adding a dibasic aromatic carboxylic acid or its derivative to a homogeneous system, heating and stirring the system to react, and then washing the system to obtain a base film resin;

[0007] (3) Using an organic solvent to dissolve the base membrane resin and adding additives, the target ion conductive membrane is obtained by a casting method after ultrasonic treatment.

[0008] The resin obtained by polymerization of quaternary aromatic amines and divalent aromatic carboxylic acids has a polybenzimidazole structure, and the main chain contains a highly stable aromatic ring skeleton, which has stronger stability in the highly oxidizing and highly acidic environment of the electrolyte. However, the conductivity of this type of substance is low, which is reflected in the reduction of voltage efficiency in practical applications and has an adverse effect on battery performance. By adding additives, an ion conduction membrane with both high vanadium ion conductivity and high conductivity is obtained, which forms a microphase separation structure in the membrane while improving the membrane conductivity, further optimizing the pore distribution of the ion conduction membrane and achieving an increase in proton conductivity.

[0009] Preferably, in step (1), the catalyst includes at least one of sulfuric acid, hydrochloric acid, polyphosphoric acid, phosphorus pentoxide, p-toluenesulfonic acid, aluminum chloride, ferric chloride, and boron trifluoride; and the quaternary aromatic amine includes at least one of 3,3'-diaminobenzidine, 3,3',4,4'-tetraaminodiphenylmethane, 3,3',4,4'-tetraaminodiphenyl ether, 3,3',4,4'-tetraaminodiphenyl sulfide, and 1,2,5,6-tetraaminonaphthalene.

[0010] Preferably, in step (1), the molar ratio of the catalyst to the tetravalent aromatic amine is 0.5-5:100.

[0011] Preferably, in step (1), the inert atmosphere is at least one of nitrogen, helium and argon introduced into the reaction vessel, and the heating condition is to increase the temperature to 150-300°C.

[0012] Preferably, in step (2), the dibasic aromatic carboxylic acid or its derivative includes at least one of 1,4-dimethyl phthalate, 1,3-phthalic acid, 1,4-phthalic acid, 1,3-phthalic acid, 1,4-phthalic acid, 1,3-phthalic acid diphenyl ester, 1,3-phthaloyl chloride, and 1,4-phthaloyl chloride.

[0013] Preferably, in step (2), dibasic aromatic carboxylic acid or its derivative is added to the homogeneous system at a molar ratio of quaternary aromatic amine to dibasic aromatic carboxylic acid or its derivative of 1-5:1-5; the heating method is heating to 40-60°C and gradually increasing the temperature to 200°C in sections within 24-36 hours.

[0014] Preferably, in step (2), the washing method is to cool the reaction product and pour it into a poor solvent, filter out the precipitate, and then wash it with deionized water to obtain the base film resin.

[0015] Preferably, in step (2), the poor solvent includes at least one of water, methanol, ethanol, isopropanol and acetone.

[0016] Preferably, in step (3), the organic solvent includes at least one of dimethyl sulfoxide, dimethylacetamide, N-methylpyrrolidone, and N,N-dimethylformamide; the additive includes at least one of bismuth vanadate, bismuth molybdate, and bismuth tungstate; and the weight ratio of the additive to the base film resin is 0.01-0.1:100.

[0017] Another aspect of the present invention discloses an application of the composite ion conductive membrane prepared by the preparation method in a liquid flow battery.

[0018] In some embodiments, the flow battery comprises one of an all-vanadium flow battery, a zinc / bromine flow battery, a zinc / iodine flow battery, an iron / chromium flow battery, or a vanadium / bromine flow battery.

[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the ion conduction membrane prepared by the present invention has good electrical properties and mechanical strength, the coulomb efficiency can reach 95.6%, the voltage efficiency can reach 93.2%, the energy efficiency can reach 87.9%, the tensile strength exceeds 110MPa, and the elongation at break is as high as 2877%. All performances are significantly higher than those of the existing ion conduction membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a surface microstructure diagram of the ion conductive membrane prepared in Example 3. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0022] Example 1: A method for preparing an ion conducting membrane is as follows:

[0023] (1) p-Toluenesulfonic acid is added to a round-bottom flask, nitrogen is introduced and stirred, 3,3'-diaminobenzidine is added to the flask, the molar ratio of p-toluenesulfonic acid to 3,3'-diaminobenzidine is 0.5:100, the temperature is raised to 150° C., and stirred for 2 h until a homogeneous system is formed;

[0024] (2) Turn off the heating, cool to room temperature, add dimethyl 1,4-phthalate, and the molar ratio of 3,3'-diaminobenzidine to dimethyl 1,4-phthalate is 1:1, stir and heat to 50°C and keep the temperature for 6 hours, then continue to heat to 100°C and keep the temperature for 6 hours, continue to heat to 150°C and keep the temperature for 6 hours, and finally heat to 200°C and keep the temperature for 6 hours to obtain a base film resin. After cooling, pour the base film resin into water, filter the precipitate, and wash the residual catalyst and unreacted products on the surface of the resin with deionized water;

[0025] (3) The base membrane resin was transferred to N-methylpyrrolidone and dissolved at a material-liquid ratio of 20 g:100 mL, bismuth vanadate was added, and the weight ratio of bismuth vanadate to base membrane resin was 0.05:100. After ultrasonic treatment, the target ion conductive membrane was obtained by casting method, such as Figure 1 shown.

[0026] Example 2: A method for preparing an ion conducting membrane is as follows:

[0027] (1) Add sulfuric acid to a round-bottom flask, introduce helium and stir, add 3,3',4,4'-tetraaminodiphenylmethane to the flask, the molar ratio of sulfuric acid to 3,3',4,4'-tetraaminodiphenylmethane is 1:100, heat to 300°C, and stir for 1 hour until a homogeneous system is formed;

[0028] (2) Turn off the heating, cool to room temperature, add 1,3-phthalic acid, 3,3',4,4'-tetraaminodiphenylmethane and 1,3-phthalic acid in a molar ratio of 1:5, stir and heat to 60°C for 8 hours, then continue to heat to 130°C for 8 hours, and continue to heat to 200°C for 8 hours to obtain a base film resin. After cooling, pour the base film resin into methanol, filter the precipitate, and wash the residual catalyst and unreacted products on the resin surface with deionized water;

[0029] (3) The base membrane resin is transferred to dimethyl sulfoxide for dissolution at a material-liquid ratio of 15 g:100 mL, bismuth molybdate is added, and the weight ratio of bismuth molybdate to the base membrane resin is 0.01:100. After ultrasonic treatment, the target ion conductive membrane is obtained by a casting method.

[0030] Example 3: A method for preparing an ion conducting membrane is as follows:

[0031] (1) Add polyphosphoric acid into a round-bottom flask, introduce argon and stir, add 3,3',4,4'-tetraaminodiphenyl ether into the flask, the molar ratio of polyphosphoric acid to 3,3',4,4'-tetraaminodiphenyl ether is 2:100, heat to 200° C., and stir for 3 h until a homogeneous system is formed;

[0032] (2) Turn off the heating, cool to room temperature, add 1,3-benzenedioic acid, the molar ratio of 3,3',4,4'-tetraaminodiphenyl ether to 1,3-benzenedioic acid is 5:1, stir and heat to 40°C and keep warm for 6 hours, then continue to heat to 100°C and keep warm for 6 hours, continue to heat to 150°C and keep warm for 6 hours, and finally heat to 200°C and keep warm for 6 hours to obtain a base film resin. After cooling, pour the base film resin into isopropanol, filter the precipitate and wash the residual catalyst and unreacted products on the surface of the resin with deionized water;

[0033] (3) The base membrane resin was transferred to dimethylacetamide for dissolution at a material-liquid ratio of 10 g:100 mL, and bismuth tungstate was added. The weight ratio of bismuth tungstate to base membrane resin was 0.1:100. After ultrasonic treatment, the target ion conductive membrane was obtained by a casting method.

[0034] Embodiment 4: All other aspects are the same as Embodiment 1, except that:

[0035] The p-toluenesulfonic acid was replaced by hydrochloric acid, and the 3,3'-diaminobenzidine was replaced by 3,3',4,4'-tetraaminodiphenyl sulfide; the molar ratio of hydrochloric acid to 3,3',4,4'-tetraaminodiphenyl sulfide was 5:100.

[0036] Substituting dimethyl 1,4-phthalate with 1,4-phthalic acid;

[0037] Pour the cooled base film resin into ethanol;

[0038] The base film resin was transferred to N,N-dimethylformamide for dissolution.

[0039] Embodiment 5: All other aspects are the same as Embodiment 1, except that:

[0040] p-Toluenesulfonic acid was replaced by phosphorus pentoxide, and 3,3'-diaminobenzidine was replaced by 1,2,5,6-tetraaminonaphthalene;

[0041] Replace dimethyl 1,4-phthalate with 1,4-benzenedicarboxylic acid;

[0042] Pour the cooled base film resin into acetone.

[0043] Embodiment 6: All other aspects are the same as those of Embodiment 1, except that:

[0044] Replace p-toluenesulfonic acid with aluminum chloride;

[0045] Replace dimethyl 1,4-phthalate with diphenyl 1,3-phthalate:

[0046] Embodiment 7: All other aspects are the same as embodiment 1, except that.

[0047] p-Toluenesulfonic acid was replaced by ferric chloride, and 3,3'-diaminobenzidine was replaced by 1,2,5,6-tetraaminonaphthalene;

[0048] Replace dimethyl 1,4-phthalate with 1,3-phthaloyl chloride;

[0049] Pour the cooled base film resin into acetone.

[0050] Embodiment 8: All other aspects are the same as Embodiment 1, except that:

[0051] p-Toluenesulfonic acid was replaced by boron trifluoride, and 3,3'-diaminobenzidine was replaced by 3,3',4,4'-tetraaminodiphenyl sulfide;

[0052] Replace dimethyl 1,4-phthalate with 1,4-phthaloyl chloride;

[0053] The base film resin was transferred to N,N-dimethylformamide for dissolution.

[0054] Embodiment 9: All other aspects are the same as Embodiment 1, except that:

[0055] The p-toluenesulfonic acid was replaced by phosphorus pentoxide.

[0056] Embodiment 10: All other aspects are the same as Embodiment 1, except that:

[0057] The bismuth vanadate was replaced by bismuth molybdate.

[0058] Comparative Example 1: The rest is the same as Example 1, except that:

[0059] No bismuth vanadate was added.

[0060] Comparative Example 2: Commercially available Nafion 117 was used as a test sample, and its thickness was the same as that of the ion conductive membrane prepared in Example 3.

[0061] The mechanical properties and electrical properties of the ion exchange membranes in Examples 1-10 and Comparative Examples 1-2 were tested as follows:

[0062] Tensile strength and elongation at break can characterize the tensile properties of the comparative examples and embodiments, thereby reflecting the mechanical strength of the comparative examples and embodiments to a certain extent. The tensile strength and elongation at break are tested by using a universal testing machine. Before testing, the comparative examples and embodiments are soaked in ultrapure water for 24 hours and then cut into 1cm×5cm sizes, placed in a test fixture, so that the longitudinal axis of the sample coincides with the center line of the upper and lower fixtures, and clamped. According to the measured tensile curve, the required load and the corresponding film thickness and width are read, and the tensile strength and elongation at break are calculated.

[0063] In order to study the practical application effects of the comparative examples and embodiments, it is necessary to conduct single cell performance tests to determine their coulombic efficiency, voltage efficiency and energy efficiency. The single cell performance test is completed by a charge and discharge test system, with a preset cutoff voltage of 1 to 1.65 V and a current density of 200 mA cm -2 .

[0064] Table 1 Performance test results of ion conductive membranes prepared by different methods

[0065]

[0066] The results in Table 1 show that the ion conducting membrane prepared by the present invention has excellent mechanical and electrical properties, and the upper limits of various properties are higher than those of existing ion conducting membranes. Moreover, the addition of bismuth-containing additives can greatly improve the performance of the ion conducting membrane.

Claims

1. A method for preparing a composite ion conducting membrane, characterized in that: The steps include: (1) Under an inert atmosphere, a catalyst and a quaternary aromatic amine are mixed, and heated and stirred to react to obtain a homogeneous system; (2) adding a dibasic aromatic carboxylic acid or its derivative to a homogeneous system, heating and stirring the system to react, and then washing the system to obtain a base film resin; (3) Using an organic solvent to dissolve the base membrane resin and adding additives, the target ion conductive membrane is obtained by a casting method after ultrasonic treatment.

2. The method for preparing the composite ion conducting membrane according to claim 1, characterized in that: In step (1), the catalyst includes at least one of sulfuric acid, hydrochloric acid, polyphosphoric acid, phosphorus pentoxide, p-toluenesulfonic acid, aluminum chloride, ferric chloride, and boron trifluoride; the quaternary aromatic amine includes at least one of 3,3'-diaminobenzidine, 3,3',4,4'-tetraaminodiphenylmethane, 3,3',4,4'-tetraaminodiphenyl ether, 3,3',4,4'-tetraaminodiphenyl sulfide, and 1,2,5,6-tetraaminonaphthalene.

3. The method for preparing the composite ion conducting membrane according to claim 1, characterized in that: In step (1), the molar ratio of the catalyst to the tetravalent aromatic amine is 0.5-5:

100.

4. The method for preparing the composite ion conducting membrane according to claim 1, characterized in that: In step (1), the inert atmosphere is at least one of nitrogen, helium and argon introduced into the reaction container, and the heating condition is to increase the temperature to 150-300°C.

5. The method for preparing the composite ion conducting membrane according to claim 1, characterized in that: In step (2), the dibasic aromatic carboxylic acid or its derivative includes at least one of 1,3-phthalic acid, 1,4-phthalic acid, 1,3-phthalic acid, 1,4-phthalic acid, 1,3-phthalic acid diphenyl ester, 1,3-phthaloyl chloride, and 1,4-phthaloyl chloride.

6. The method for preparing the composite ion conducting membrane according to claim 1, characterized in that: In step (2), dibasic aromatic carboxylic acid or its derivative is added to the homogeneous system at a molar ratio of quaternary aromatic amine to dibasic aromatic carboxylic acid or its derivative of 1-5:1-5; the heating method is to heat to 40-60°C and gradually increase the temperature to 200°C in sections within 24-36 hours.

7. The method for preparing the composite ion conducting membrane according to claim 1, characterized in that: In step (2), the washing method is to cool the reaction product and pour it into a poor solvent, filter out the precipitate, and then wash it with deionized water to obtain the base film resin.

8. The method for preparing a composite ion conducting membrane according to claim 7, characterized in that: In step (2), the poor solvent includes at least one of water, methanol, ethanol, isopropanol, and acetone.

9. The method for preparing a composite ion conducting membrane according to claim 1, characterized in that: In step (3), the organic solvent includes at least one of dimethyl sulfoxide, dimethylacetamide, N-methylpyrrolidone, and N,N-dimethylformamide; the additive includes at least one of bismuth vanadate, bismuth molybdate, and bismuth tungstate; and the weight ratio of the additive to the base film resin is 0.01-0.1:

100.

10. Use of the composite ion conductive membrane prepared by the preparation method according to any one of claims 1 to 9 in a liquid flow battery.

Citation Information

Patent Citations

  • Poly(arylene ether benzimidazole) ion exchange membrane and preparation method thereof and all-vanadium redox flow battery

    CN102044648A

  • Inorganic nanoparticle in-situ modified polybenzimidazole proton exchange membrane and preparation method thereof

    CN103700874A

  • Bismuth vanadate / graphite-phase carbon nitride composite material, and preparation method and application thereof

    CN108325554A

  • Device and method for synthesizing ammonia through photoelectrocatalysis nitrogen fixation

    CN110079816A

  • Compound, cross-linked material thereof, double cross-linked polymer thereof, and electrolyte membrane, electrode for fuel cell and fuel cell including same

    US20110189581A1